Budgetary control on the example of the residential community - Juras, Bartłomiej; Czerny, Małgorzata (Kontrola budżetowa na przykładzie wspólnoty mieszkaniowej, 2018)
The article discusses a role of budgetary control as a method of financial management in the housing community during the period of 2011-2015. As the research methods there were used the analysis of the budgets, as well as deductive and inductive reasoning for conclusions. The analysis of the budgets and their implementation in 2011-2015 shows that budgetary control is successfully used to manage community’s finances. It allowed the community to reduce certain categories of costs significantly. The analysis undertaken by the community venture shows that manifestations of budgetary control are present in its activities, taking into account feed-back and also feed-forward
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 503, s. 179-194
Keywords: budgeting; budgetary control; cost; financial management; residential community; budżetowanie; kontrola budżetowa; koszt; zarządzanie finansami; wspólnota mieszkaniowa